Recurrent hydatid disease, a case report and literature review - Lee, Frances M.; Gaszynski, Rafael; Merrett, Neil (International Surgery Journal, 2021)
Hydatid disease (HD) remains endemic in Australia, with estimated incidence highest in rural and indigenous populations. Its recurrence is defined by new active cysts arising after appropriate therapy, and affects anywhere between 2-25% of total cases. Available treatment options include surgical resection, percutaneous drainage, and chemotherapy. Interestingly, their individual contributions to long-term minimisation of recurrence are scarcely described in the literature. We present a unique case of a 27-year-old female with recurrent hepatic HD requiring repeat operations and long-term chemotherapy. Prevention and treatment of recurrent HD requires careful evaluation of a multitude of factors, including disease characteristics, patient attributes, physician expertise and availability of resources. Consistent long-term follow up is required to better ascertain the long-term efficacy of reported treatment modalities for preventing recurrence. Despite a growing body of research looking at treatment of HD, there remains a considerable amount of controversy regarding most effective approach for minimising and preventing its recurrence.